Weakened future surface warming in China due to national planned afforestation through biophysical feedback - Shuaifeng Song; Xiaodong Yan; Xuezhen Zhang; Zhibo Gao; Wenqiang Xie (npj Climate and Atmospheric Science)
Abstract A national-level afforestation plan has been announced by the Chinese government to combat global warming through carbon sequestration. However, the biophysical feedback of afforestation under future climate scenarios has not yet been assessed. Here, using the Weather Research and Forecast model (WRF) nested by the bias-corrected MPI-ESM1-2-HR model, we simulated how future afforestation regulated the land surface temperature (LST) in China. The results show that afforestation induces a significant cooling effect over the period 2041–2060 under the SSP2-4.5 scenario, in particular in the cold season. The additional cooling effect offsets about 3.69% of the projected LST increase due to global warming and even overcompensates the LST increase in southwestern China. On the diurnal cycles, afforestation induces daytime cooling effects of −0.21 °C caused by increased latent heat fluxes, while nighttime warming effects of 0.05 °C induced mainly by cloud feedback. Our findings highlight the importance of the scientific identification of afforestation areas when developing land-management strategies and biophysical feedback for climate change mitigation.